Effect of the degree of hill slope on acute downhill running velocity and acceleration - Ebben, W. P.; Davies, J. A.; Clewien, R. W. (The Journal of Strength and Conditioning Research, 2008)
This study analyzes the effects of hill slope on acute overspeed running. This study considers both acceleration and supramaximal velocity. Forty-four athletes ran 40-yard sprints, on 5 different hill slopes, ranging from 2.1° to 6.9°. Forty-yard sprint times and 10-yard split times were recorded using the Brower Timing System Speedtrap II. Analysis reveals that 40-yard and 10-yard sprints performed on hill slopes of approximately 5.8° were optimal compared to flatland running and the other slopes assessed. Sprinting on a 5.8° slope increased the subjects' maximal speed by 7.09% ± 3.66% and increased the subjects' acceleration by 6.54% ± 1.56%. Strength and conditioning professionals who train athletes for speed should develop and use overspeed hills or platforms with slopes of approximately 5.8° in order to maximize acute sprinting velocity and acceleration.